Erroneous formulation of delayed-release omeprazole capsules: alert for importing countries - Mohammad Sofiqur Rahman; Naoko Yoshida; Hirohito Tsuboi; Tep Keila; Tey Sovannarith; Heng Bun Kiet; Eav Dararth; Theingi Zin; Tsuyoshi Tanimoto; Kazuko Kimura (BMC, 2017)
Abstract Background Poor drug quality is a matter of serious concern, especially in countries where drug regulation and law enforcement are constrained by limited resources. This study was carried out to investigate the cause of quality failure of omeprazole in Cambodia in 2010 and Myanmar in 2014. Methods We conducted pharmacopoeial quantity, content uniformity and dissolution tests of 156 samples of omeprazole capsules collected in Cambodia in 2010 and Myanmar in 2014. High failure rates were found, especially in dissolution testing, and detailed investigation of several unacceptable samples was carried out by means of in-vitro dissolution profiling, scanning electron microscopy (SEM) and X-ray computed tomography (X-ray CT) to identify the cause of failure. Results Dissolution profiling with and without the acid stage showed that acid caused premature omeprazole release, indicating that the enteric coating of the omeprazole granules was ineffective. SEM examination of two failed samples revealed cracked and broken granules mixed with apparently intact omeprazole granules in the capsule. X-ray CT examination indicated that some granules of failed samples completely lacked enteric coating, and others had incomplete and non-uniform enteric coating or malformation. Conclusions Omeprazole capsules collected in Myanmar and Cambodia showed high failure rates in pharmacopoeial tests, especially dissolution tests. Some samples were found to have ineffective or absent enteric coating of the granules, resulting in premature dissolution and degradation in acidic conditions. This is a potentially serious public health issue that needs to be addressed by regulatory authorities in Cambodia and Myanmar, possibly through a collaborative initiative with manufacturers.